FAKTOR PENYEBAB PASANGAN USIA SUBUR DALAM MEMILIH ALAT KONTRASEPSI DI PUSKESMAS PASAR MATANGGOR KECAMATAN BATANG ONANG KABUPATEN PALUTA TAHUN 2016 - Damanik, Dady Hidayah; Harahap, Yusnita Ramadhona (Universitas Aufa Royhan, 2016)
Contraception is a way to prevented or conception, equipment or medicines. Conception(fertilization) is the meeting between the egg (ovum) wife with the sperm (spermatozoon) husband inthe egg. Contraceptives must have good terms of, among others, secure, reliable, simple (as much aspossible do not need to be done by a doctor), inexpensive, can be accepted by many people and can beused in the long term.This study was a qualitative research that aims to determine the cause of PUS selectingcontraceptives in Puskesmas Pasar Matanggor Batang Onang subdistrict of Paluta district 2016. Datacollection methods used in this study is the in-depth interviews, the number of research informant as 5peoples.The results showed that factors cause couples of childbearing age in selecting contraceptionthey use are based on convenience contraseption time band is used, easy to use and to consider alsothe husband wishes.